Serum Uric Acid: A Risk Signal and a Treatment Target for Essential Hypertension - Zhang, MD, PhD, Weili; Hui, MD, PhD, Rutai (North American Journal of Medicine and Science, 2011)
Uric acid is the end product of purine metabolism in humans. During the past several decades, lifestyle and dietary changes and the aging of overall population contribute to progressively rising of serum uric acid levels. Although a number of epidemiologic data has suggested that elevated serum uric acid levels are associated with increased risk for hypertension and cardiovascular diseases, the causal role of uric acid in the development of hypertension is still inconclusive. In this review, we summarize experimental and population studies on uric acid and possible links to hypertension and the pathogenic mechanisms. We also discuss environmental factors and genetic variations that affect serum uric acid levels and disease risks.